Low Self-Control, Social Learning, and Texting while Driving - Meldrum, Ryan Charles (American journal of criminal justice, 2019)
Despite the known implications of texting while driving for reducing driver alertness and increasing traffic accidents, investigating the potential causes of the behavior is something that criminologists have only recently started to investigate. The current study builds on this small body of research by assessing whether low self-control is associated with the frequency of texting while driving and, further, whether this association is moderated by perceptions of the texting habits of other drivers and best friends. Results based on data collected from a sample of 469 young adults indicate that low self-control is positively associated with the frequency of texting while driving. In addition, this association is amplified by an individual’s perceptions of the proportion of other drivers who engage in texting while driving, but not by the texting and driving habits of best friends.